First principle calculation of NOx adsorption on ATiO3 perovskites surfaces - Abrahamsson, Brita (My University, 2015)
A promising solution to control NOx-emissions in lean-burn engines is combined NOx- trap and NH3-SCR catalysis, where NOx is trapped in a storage material at low temperatures and then released and reduced by ammonia at temperatures around 150-200 C. Here, adsorption of NOx on perovskites with the structural formula ATiO3, A = Ca, Sr, Ba, have been studied within the Density Functional Theory, to investigate the compounds' capability of storing NOx at desired temperatures. Comparisons are made with adsorption on alkali-earth metal oxide surfaces. DFT is employed with local basis functions using the PBE-functional and the perovskite-surfaces are modelled by the supercell periodic slab approach. The adsorption of NO is found to be a weak physorption process, with desorption temperatures at around 250 K for AO-terminated Ba- and SrTiO3. The interaction with NO2 is stronger, and depends on the electropositivety of A (Ba>Sr>Ca). Dramatic cooperative effects are observed for pairwise adsorption of NO and NO2. Negative charge is transferred from surface anion to NO2 upon pairadsorption, creating nitrite-like structures for both NO2 and O-NO. The cooperative effect holds also for NO and O2, with slightly lower adsorption energies.
Keywords: Fysik; Grundläggande vetenskaper; Hållbar utveckling; Innovation och entreprenörskap (nyttiggörande); Physical Sciences; Basic Sciences; Sustainable Development; Innovation & Entrepreneurship